Driving Teachers as Catalysts of Innovation: A Literature Review on Teacher Leadership in Indonesia’s Merdeka Belajar Reform - Maslina Maslina; Aman Simaremare (MASI Mandiri Edukasi, 2025)
This study explores the role of Driving Teachers (Guru Penggerak) in advancing innovative work behavior among educators within the context of Indonesia’s Merdeka Belajar (Freedom to Learn) policy. Employing a qualitative approach through literature review, this paper synthesizes insights from policy documents, scholarly publications, and training frameworks to understand how teacher leadership, reflective practice, and technological adaptation contribute to educational transformation. The review highlights that Driving Teachers act not only as classroom facilitators but also as mentors, collaborators, and change agents within professional learning communities. Their ability to foster student-centered, inclusive, and contextually relevant instruction is central to the success of Merdeka Belajar. The analysis also identifies challenges such as policy-practice gaps, limited institutional support, and the need for sustained professional development. This study offers practical implications for education policymakers, school leaders, and teacher educators in enhancing teacher capacity and system-wide innovation. It also contributes to the academic discourse on teacher agency and reform in emerging education systems.